Redox‐State‐Mediated Regulation of Cytochrome c Release in Apoptosis Revealed by Surface‐Enhanced Raman Scattering on Nickel Substrates. (26th September 2019) - Zhu, Jinyu; Jiang, Muwei; Ma, Hao; Zhang, Haijing; Cheng, Weina; Li, Junbo; Cai, Linjun; Han, Xiao Xia; Zhao, Bing
Abstract: The interaction of cytochrome c (Cyt c) with cardiolipin (CL) is believed to play an important role in the initial events of apoptosis. Herein, we investigate the structural changes of CL‐bound Fe 2+ Cyt c and the correlation with Cyt c release through surface‐enhanced Raman spectroscopy (SERS) on nickel substrates. The SERS results together with molecular dynamics simulation reveal that Fe 2+ Cyt c undergoes autoxidation and a relatively larger conformational alteration after binding with CL, inducing higher peroxidase activity of Cyt c and higher permeability of the CL membrane compared with those induced by the Fe 3+ Cyt c. The proapoptotic activity and SERS effect of the Ni nanostructures allow the in situ study of the redox‐state‐dependent Cyt c release from isolated mitochondria, which reveals for the first time that the ferrous state of Cyt c most likely plays a more important role in triggering apoptosis. Abstract : Tragbare Zustände : Durch Anwendung oberflächenverstärkter Raman‐Spektroskopie (SERS) auf Nickelträger wurde nachgewiesen, dass der Redoxzustand von Cytochrom c dessen Freisetzung aus Mitochondrien in apoptotischen Zellen reguliert. Die SERS‐Daten und Moleküldynamiksimulationen zeigen, dass der Eisen(II)‐Zustand von Cytochrom c höchstwahrscheinlich eine wichtigere Rolle beim Auslösen der Apoptose spielt.